Pervaporation membrane doped with MOF-on-MOF core-shell structure filler and preparation method thereof

By doping Zr-MOF@Cu-MOF filler with MOF-on-MOF core-shell structure in the polyvinyl alcohol and polyacrylic acid composite film, the problems of low permeability, low separation coefficient and poor swelling resistance when separating DMF waste liquid are solved, and higher separation efficiency and mechanical strength are achieved.

CN119656888APending Publication Date: 2025-03-21CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411835840.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, the polyvinyl alcohol film has problems such as low permeability, low separation coefficient, and poor swelling resistance of the polyvinyl alcohol film when separating the DMF waste liquid.

Method used

By doping Zr-MOF@Cu-MOF filler with MOF-on-MOF core-shell structure in the polyvinyl alcohol and polyacrylic acid composite film, the hydrophilicity and structural stability of the film are improved, thereby enhancing the selectivity and separation efficiency of water molecules.

Benefits of technology

The permeability flux and separation coefficient of the composite film are significantly improved, the mechanical strength and swelling resistance of the film are enhanced, and the insufficient performance of the polyvinyl alcohol film is effectively solved when separating the aqueous DMF solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656888A_ABST
    Figure CN119656888A_ABST
Patent Text Reader

Abstract

The invention discloses a pervaporation membrane doped with an MOF-on-MOF core-shell structure filler. The pervaporation membrane comprises an organic polymer base membrane and a Zr-MOF coated Cu-MOF filler which is dispersed in the organic polymer base membrane and has an MOF-on-MOF core-shell structure. The invention also discloses a preparation method of the pervaporation membrane, which specifically comprises the following steps: mixing polyvinyl alcohol, polyacrylic acid and water, and heating to obtain a polyvinyl alcohol aqueous solution; adding the Zr-MOF coated Cu-MOF filler into a polyvinyl alcohol aqueous solution, uniformly stirring to obtain a membrane casting solution, casting to form a membrane, and curing to obtain the pervaporation membrane. According to the preparation method, Zr-MOF (at) Cu-MOF with an MOF-on-MOF core-shell structure is doped in the polyvinyl alcohol and polyacrylic acid composite membrane, so that the hydrophilicity of the membrane can be greatly improved, and meanwhile, a channel with higher selectivity to water molecules can be formed in the membrane, so that the permeation flux and the separation coefficient of the membrane during separation of a DMF (Dimethyl Formamide) aqueous solution are improved, and the membrane has good separation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a pervaporation membrane doped with a MOF-on-MOF core-shell structure filler and also relates to a preparation method of the pervaporation membrane. Background Art

[0002] N,N-dimethylformamide (DMF) is a polar (hydrophilic) aprotic solvent with a high boiling point (153°C). It is often used as a solvent because it is miscible with water and most organic solvents. However, traditional separation methods such as distillation have the problems of high cost and energy consumption and incomplete separation in treating DMF waste liquid. Pervaporation membrane separation technology, as an emerging membrane separation technology, can effectively solve the above problems. However, in the prior art, polyvinyl alcohol membranes have the problems of low permeability flux, low separation coefficient and poor swelling resistance when separating DMF waste liquid (DMF / H2O). Compared with polyvinyl alcohol membranes, the separation performance of the current mixed matrix membranes doped with MOFs has limited improvement, and the doped MOFs particles are prone to nanoparticle cluster aggregation, which in turn affects the separation performance. Summary of the invention

[0003] Purpose of the invention: The purpose of the present invention is to provide a pervaporation membrane doped with a MOF-on-MOF core-shell structure filler. When the pervaporation membrane is used to treat DMF waste liquid, on the one hand, the membrane has good hydrophilicity and can greatly improve the adsorption capacity of water, thereby effectively improving the separation efficiency of the membrane. On the other hand, the pore structure formed in the membrane can be more conducive to the passage of water molecules, thereby greatly improving the selectivity of the membrane for water. Another purpose of the present invention is to provide a method for preparing the above-mentioned pervaporation membrane.

[0004] Technical solution: The pervaporation membrane doped with MOF-on-MOF core-shell structure filler described in the present invention includes an organic polymer base membrane and a Zr-MOF@Cu-MOF filler with a MOF-on-MOF core-shell structure dispersed in the organic polymer base membrane.

[0005] The organic polymer base film is a composite film formed by polyvinyl alcohol and polyacrylic acid (cross-linking effect, polyacrylic acid is often added in the synthesis of polyvinyl alcohol film); wherein, in the composite film, the mixing mass ratio of polyvinyl alcohol and polyacrylic acid is 8-9:1.

[0006] Wherein, in the composite film, the doping amount of Zr-MOF@Cu-MOF filler is 1% to 5% of the total mass of polyvinyl alcohol and polyacrylic acid.

[0007] The preparation method of the above-mentioned pervaporation membrane is specifically as follows: polyvinyl alcohol, polyacrylic acid and water are mixed and heated to obtain a polyvinyl alcohol aqueous solution; Zr-MOF@Cu-MOF filler is added to the polyvinyl alcohol aqueous solution, stirred evenly to obtain a casting liquid, cast into a membrane, and solidified to obtain a pervaporation membrane.

[0008] Wherein, the heating temperature is 80-90° C., and the heating time is 2-6 hours.

[0009] Wherein, the curing temperature is 20-30°C, and the curing time is not less than 24h.

[0010] The Zr-MOF@Cu-MOF filler is prepared by the following method, which comprises the following steps:

[0011] (1) Preparation of Zr-MOF: Dissolve zirconium tetrachloride and an organic ligand in N,N-dimethylformamide, mix well, add acetic acid, subject the mixed solution to a hydrothermal reaction at high temperature, wash and dry after the reaction to obtain Zr-MOF;

[0012] (2) Zr-MOF is ultrasonically dispersed in DMF, and then copper nitrate, trimesic acid and DMF are added thereto. The mixed solution is subjected to a hydrothermal reaction at high temperature to obtain Zr-MOF@Cu-MOF with a MOF-on-MOF core-shell structure.

[0013] Wherein, in step (1), the organic ligand is one of terephthalic acid, 2-aminoterephthalic acid or 2,5-dihydroxyterephthalic acid; and the molar ratio of zirconium tetrachloride to the organic ligand is 0.5 to 3:1.

[0014] Wherein, in step (1), the temperature of the hydrothermal reaction is 120-125° C., and the hydrothermal reaction time is 70-72 h.

[0015] Wherein, in step (2), the molar ratio of copper nitrate to trimesic acid is 3:1 to 1.5.

[0016] Wherein, in step (2), the temperature of the hydrothermal reaction is 120-120° C., and the hydrothermal reaction time is 96-98 h.

[0017] The present invention uses Zr-MOF as a template, and introduces metal ions and organic ligands externally to carry out secondary growth of MOFs. Under the condition of high lattice compatibility, secondary MOFs can effectively nucleate and grow on the primary MOFs substrate to form a MOF-on-MOF core-shell structure. Compared with a single MOFs material, the MOF-on-MOF heterostructure of the present invention can provide higher stability through dynamic coordination bonds, and can further improve the hydrophilicity of the structure.

[0018] The present invention dopes Zr-MOF@Cu-MOF with a MOF-on-MOF core-shell structure into a polyvinyl alcohol and polyacrylic acid composite membrane, thereby effectively improving the hydrophilicity of the MOF mixed matrix membrane, making the membrane more easily combined with water molecules, increasing the adsorption content of water, achieving the membrane's preferential selectivity for water molecules while improving the separation efficiency; secondly, the doped Zr-MOF@Cu-MOF with a MOF-on-MOF core-shell structure can form a channel in the middle of the membrane that is easier for small molecules (water molecules) to pass through, thereby further improving the membrane's preferential selectivity for water molecules; then, since Zr-MOF and Cu-MOF select organic ligands with the same functional groups, Cu-MOF can grow in an orderly manner on the surface of Zr-MOF, enhancing the stability of the system structure, enabling it to stably exist in acidic conditions and water, and effectively increasing the mechanical strength and swelling resistance of the membrane.

[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: by doping Zr-MOF@Cu-MOF with a MOF-on-MOF core-shell structure in the polyvinyl alcohol and polyacrylic acid composite membrane, the present invention can greatly increase the number of hydrophilic groups inside the composite membrane, thereby increasing the hydrophilicity of the composite membrane, and at the same time can also form channels in the membrane that are more selective for water molecules, thereby improving the permeation flux and separation coefficient of the membrane when separating DMF aqueous solution, so that the membrane has good separation performance; at the same time, doping Zr-MOF@Cu-MOF with a MOF-on-MOF core-shell structure can also improve the mechanical strength of the composite membrane and extend its service life. Therefore, the pervaporation membrane of the present invention effectively solves the problems of low permeation flux, low separation coefficient and poor swelling resistance of the polyvinyl alcohol membrane in the prior art when separating specific material systems (DMF / H2O). BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A transmission electron micrograph of Zr-MOF@Cu-MOF particles having a MOF-on-MOF core-shell structure prepared in Example 1;

[0021] Figure 2 A transmission electron micrograph of Zr-MOF@Cu-MOF particles having a MOF-on-MOF core-shell structure prepared in Example 2;

[0022] Figure 3 This is a transmission electron micrograph of the Zr-MOF@Cu-MOF particles with a MOF-on-MOF core-shell structure prepared in Example 3. DETAILED DESCRIPTION

[0023] Example 1

[0024] The preparation method of the pervaporation membrane of the present invention comprises the following steps:

[0025] (1) Zr-MOF@Cu-MOF with MOF-on-MOF core-shell structure:

[0026] (1.1) Zirconium tetrachloride and terephthalic acid in a molar ratio of 1:1 were added to 60 mL of N,N-dimethylformamide, and 3 mL of acetic acid was added after ultrasonication for 5 min. After magnetic stirring for 0.5 h, the mixed solution was sealed in a polytetrafluoroethylene hydrothermal reactor and subjected to hydrothermal reaction at 120 °C for 72 h.

[0027] (1.2) After the sample is cooled naturally, it is centrifuged, washed with DMF and methanol three times respectively, and then dried at 60°C for 24 hours to obtain Zr-MOF;

[0028] (1.3) 0.1 g Zr-MOF was ultrasonically dispersed in 10 mL DMF, and then copper nitrate and trimesic acid in a molar ratio of 3:1 and 50 mL DMF were added thereto. After magnetic stirring for 0.5 h, the mixed solution was sealed in a polytetrafluoroethylene hydrothermal reactor and hydrothermally reacted at 120 °C for 96 h.

[0029] (1.4) After the sample was cooled naturally, it was centrifuged, washed with distilled water three times, and dried at 80 °C for 10 h to obtain Zr-MOF@Cu-MOF with a MOF-on-MOF core-shell structure;

[0030] (2) polyvinyl alcohol (polyvinyl alcohol molecular weight of 1500-5000, alcoholysis degree of 50%-88%), polyacrylic acid (solid powder, polyacrylic acid molecular weight of 2000-45000) and water are mixed in a mass ratio of 9:1:10 to obtain a mixture; 50 g of the mixture is weighed, stirred at 80° C. for 2 h, and after the polyvinyl alcohol is fully dissolved, the mixture is cooled to room temperature to obtain a polyvinyl alcohol aqueous solution;

[0031] (3) Zr-MOF@Cu-MOF was mixed with a polyvinyl alcohol aqueous solution and dispersed evenly by ultrasound to obtain a mixed solution; 15 g of the mixed solution was then weighed into a glass culture dish and allowed to stand at room temperature for solidification and cross-linking, and the membrane was removed after 24 hours to obtain a pervaporation membrane; wherein the mass fraction of Zr-MOF@Cu-MOF in the mixed solution was 5%, that is, the amount of Zr-MOF@Cu-MOF added was 5% of the mass of the polyvinyl alcohol aqueous solution.

[0032] The pervaporation membrane prepared in Example 1 was used to separate a 15 wt.% N,N-dimethylformamide aqueous solution, and the permeation flux was 62.2 g·m -2 ·h -1 , the separation factor was 13.1. After long-term operation for 200 h, there was no significant change in the permeation flux and separation factor.

[0033] Example 2

[0034] The preparation method of the pervaporation membrane of the present invention comprises the following steps:

[0035] (1) Zr-MOF@Cu-MOF with MOF-on-MOF core-shell structure:

[0036] (1.1) Zirconium tetrachloride and 2-aminoterephthalic acid in a molar ratio of 2:1 were added to 60 mL of N,N-dimethylformamide, and 4 mL of acetic acid was added after ultrasonication for 5 min. After magnetic stirring for 0.5 h, the mixed solution was sealed in a polytetrafluoroethylene hydrothermal reactor and subjected to hydrothermal reaction at 120 °C for 72 h.

[0037] (1.2) After the sample is cooled naturally, it is centrifuged, washed with DMF and methanol three times respectively, and then dried at 60°C for 24 hours to obtain Zr-MOF;

[0038] (1.3) 0.1 g Zr-MOF was ultrasonically dispersed in 10 mL DMF, and then copper nitrate and trimesic acid in a molar ratio of 3:1 and 50 mL DMF were added thereto. After magnetic stirring for 0.5 h, the mixed solution was sealed in a polytetrafluoroethylene hydrothermal reactor and hydrothermally reacted at 120 °C for 96 h.

[0039] (1.4) After the sample was cooled naturally, it was centrifuged, washed with distilled water three times, and dried at 80 °C for 10 h to obtain Zr-MOF@Cu-MOF with a MOF-on-MOF core-shell structure;

[0040] (2) polyvinyl alcohol (polyvinyl alcohol molecular weight of 1500-5000, alcoholysis degree of 50%-88%), polyacrylic acid (solid powder, polyacrylic acid molecular weight of 2000-45000) and water are mixed in a mass ratio of 9:1:10 to obtain a mixture; 50 g of the mixture is weighed, stirred at 80° C. for 2 h, and after the polyvinyl alcohol is fully dissolved, the mixture is cooled to room temperature to obtain a polyvinyl alcohol aqueous solution;

[0041] (3) Zr-MOF@Cu-MOF was mixed with a polyvinyl alcohol aqueous solution and dispersed evenly by ultrasound to obtain a mixed solution; 15 g of the mixed solution was then weighed into a glass culture dish and allowed to stand at room temperature for solidification and cross-linking, and the membrane was removed after 24 hours to obtain a pervaporation membrane; wherein the mass fraction of Zr-MOF@Cu-MOF in the mixed solution was 5%, that is, the amount of Zr-MOF@Cu-MOF added was 5% of the mass of the polyvinyl alcohol aqueous solution.

[0042] The pervaporation membrane prepared in Example 2 was used to separate a 15 wt.% N,N-dimethylformamide aqueous solution, and the permeation flux was 65.7 g·m-2 ·h -1 , the separation factor was 12.1. After long-term operation for 200 h, there was no significant change in the permeation flux and separation factor.

[0043] Example 3

[0044] The preparation method of the pervaporation membrane of the present invention comprises the following steps:

[0045] (1) Zr-MOF@Cu-MOF with MOF-on-MOF core-shell structure:

[0046] (1.1) Zirconium tetrachloride and 2,5-dihydroxyterephthalic acid in a molar ratio of 3:1 were added to 60 mL of λN,N-dimethylformamide, and 5 mL of acetic acid was added after ultrasonication for 5 min. After magnetic stirring for 0.5 h, the mixed solution was sealed in a polytetrafluoroethylene hydrothermal reactor and subjected to hydrothermal reaction at 120 °C for 72 h.

[0047] (1.2) After the sample is cooled naturally, it is centrifuged, washed with DMF and methanol three times respectively, and then dried at 60°C for 24 hours to obtain Zr-MOF;

[0048] (1.3) 0.1 g Zr-MOF was ultrasonically dispersed in 10 mL DMF, and then copper nitrate and trimesic acid in a molar ratio of 3:1 and 50 mL DMF were added thereto. After magnetic stirring for 0.5 h, the mixed solution was sealed in a polytetrafluoroethylene hydrothermal reactor and hydrothermally reacted at 120 °C for 96 h.

[0049] (1.4) After the sample was cooled naturally, it was centrifuged, washed with distilled water three times, and dried at 80 °C for 10 h to obtain Zr-MOF@Cu-MOF with a MOF-on-MOF core-shell structure;

[0050] (2) polyvinyl alcohol (polyvinyl alcohol molecular weight of 1500-5000, alcoholysis degree of 50%-88%), polyacrylic acid (solid powder, polyacrylic acid molecular weight of 2000-45000) and water are mixed in a mass ratio of 9:1:10 to obtain a mixture; 50 g of the mixture is weighed, stirred at 80° C. for 2 h, and after the polyvinyl alcohol is fully dissolved, the mixture is cooled to room temperature to obtain a polyvinyl alcohol aqueous solution;

[0051] (3) Zr-MOF@Cu-MOF was mixed with a polyvinyl alcohol aqueous solution and dispersed evenly by ultrasound to obtain a mixed solution; 15 g of the mixed solution was then weighed into a glass culture dish and allowed to stand at room temperature for solidification and cross-linking, and the membrane was removed after 24 hours to obtain a pervaporation membrane; wherein the mass fraction of Zr-MOF@Cu-MOF in the mixed solution was 5%, that is, the amount of Zr-MOF@Cu-MOF added was 5% of the mass of the polyvinyl alcohol aqueous solution.

[0052] The pervaporation membrane prepared in Example 3 was used to separate a 15 wt.% N,N-dimethylformamide aqueous solution, and the permeation flux was 73.1 g·m -2 ·h -1 , the separation factor was 11.2. After 200 h of continuous operation, there was no significant change in the permeation flux and separation factor.

[0053] Comparative Example 1

[0054] A method for preparing a pervaporation membrane comprises the following steps:

[0055] (1) Zirconium tetrachloride and terephthalic acid in a molar ratio of 3:1 were added to 60 mL of N,N-dimethylformamide, and 5 mL of acetic acid was added thereto after ultrasonic treatment for 5 minutes. After magnetic stirring for 0.5 hours, the mixed solution was sealed in a polytetrafluoroethylene hydrothermal reactor and subjected to hydrothermal reaction at 120°C for 72 hours. After the sample was cooled naturally, it was centrifuged, washed with DMF and methanol for 3 times respectively, and then dried at 60°C for 24 hours to obtain Zr-MOF.

[0056] (2) polyvinyl alcohol (polyvinyl alcohol molecular weight of 1500-5000, alcoholysis degree of 50%-88%), polyacrylic acid (solid powder, polyacrylic acid molecular weight of 2000-45000) and water are mixed in a mass ratio of 9:1:10 to obtain a mixture; 50 g of the mixture is weighed, stirred at 80° C. for 2 h, and after the polyvinyl alcohol is fully dissolved, the mixture is cooled to room temperature to obtain a polyvinyl alcohol aqueous solution;

[0057] (3) Zr-MOF is mixed with a polyvinyl alcohol aqueous solution and dispersed evenly by ultrasound to obtain a mixed solution; then 15 g of the mixed solution is weighed into a glass culture dish and allowed to stand at room temperature for solidification and cross-linking, and the membrane is removed after 24 hours to obtain a pervaporation membrane; wherein the mass fraction of Zr-MOF in the mixed solution is 5%, that is, the amount of Zr-MOF added is 5% of the mass of the polyvinyl alcohol aqueous solution.

[0058] The pervaporation membrane prepared in Comparative Example 1 was used to separate a 15 wt.% N,N-dimethylformamide aqueous solution, and the permeation flux was 58.2 g·m -2 ·h -1 , the separation factor was 9.1. After 154 h of continuous operation, the permeation flux and separation factor began to change (decline).

[0059] Comparative Example 2

[0060] A method for preparing a pervaporation membrane comprises the following steps:

[0061] (1) Preparation of Cu-MOF: copper nitrate and trimesic acid in a molar ratio of 3:1 were added to 50 mL of DMF, and the mixed solution was sealed in a polytetrafluoroethylene hydrothermal reactor after magnetic stirring for 0.5 h, and hydrothermally reacted at 120 °C for 96 h; after the sample was cooled naturally, it was centrifuged, washed with distilled water for 3 times, and dried at 80 °C for 10 h to obtain Cu-MOF;

[0062] (2) polyvinyl alcohol (polyvinyl alcohol molecular weight of 1500-5000, alcoholysis degree of 50%-88%), polyacrylic acid (solid powder, polyacrylic acid molecular weight of 2000-45000) and water are mixed in a mass ratio of 9:1:10 to obtain a mixture; 50 g of the mixture is weighed, stirred at 80° C. for 2 h, and after the polyvinyl alcohol is fully dissolved, the mixture is cooled to room temperature to obtain a polyvinyl alcohol aqueous solution;

[0063] (3) Cu-MOF is mixed with a polyvinyl alcohol aqueous solution and dispersed evenly by ultrasound to obtain a mixed solution; then 15 g of the mixed solution is weighed into a glass culture dish and allowed to stand at room temperature for solidification and cross-linking, and the membrane is removed after 24 hours to obtain a pervaporation membrane; wherein the mass fraction of Cu-MOF in the mixed solution is 5%, that is, the amount of Cu-MOF added is 5% of the mass of the polyvinyl alcohol aqueous solution.

[0064] The pervaporation membrane prepared in Comparative Example 2 was used to separate a 15 wt.% N,N-dimethylformamide aqueous solution, and the permeation flux was 48.2 g·m -2 ·h -1 , the separation factor was 6.5. After 146 h of continuous operation, the permeation flux and separation factor began to change (decline).

[0065] Comparative Example 3

[0066] A method for preparing a pervaporation membrane comprises the following steps:

[0067] (1) Preparation of Zr-MOF: Zirconium tetrachloride and terephthalic acid in a molar ratio of 3:1 were added to 60 mL of N,N-dimethylformamide, and 5 mL of acetic acid was added thereto after ultrasonic treatment for 5 min. After magnetic stirring for 0.5 h, the mixed solution was sealed in a polytetrafluoroethylene hydrothermal reactor and subjected to hydrothermal reaction at 120 °C for 72 h. After the sample was cooled naturally, it was centrifuged, washed with DMF and methanol three times respectively, and then dried at 60 °C for 24 h to obtain Zr-MOF.

[0068] (2) Preparation of Cu-MOF: copper nitrate and trimesic acid in a molar ratio of 3:1 were added to 50 mL of DMF, and the mixed solution was sealed in a polytetrafluoroethylene hydrothermal reactor after magnetic stirring for 0.5 h, and hydrothermally reacted at 120 °C for 96 h; after the sample was naturally cooled, it was centrifuged, washed with distilled water for 3 times, and dried at 80 °C for 10 h to obtain Cu-MOF;

[0069] (3) polyvinyl alcohol (polyvinyl alcohol molecular weight of 1500-5000, alcoholysis degree of 50%-88%), polyacrylic acid (solid powder, polyacrylic acid molecular weight of 2000-45000) and water are mixed in a mass ratio of 9:1:10 to obtain a mixture; 50 g of the mixture is weighed, stirred at 80° C. for 2 h, and after the polyvinyl alcohol is fully dissolved, the mixture is cooled to room temperature to obtain a polyvinyl alcohol aqueous solution;

[0070] (4) Zr-MOF, Cu-MOF and polyvinyl alcohol aqueous solution are mixed and uniformly dispersed by ultrasound to obtain a mixed solution; then 15 g of the mixed solution is weighed into a glass culture dish, and allowed to stand at room temperature for solidification and cross-linking, and the membrane is removed after 24 hours to obtain a pervaporation membrane; wherein the total mass fraction of Zr-MOF and Cu-MOF in the mixed solution is 5%, that is, the total amount of Zr-MOF and Cu-MOF added is 5% of the mass of the polyvinyl alcohol aqueous solution.

[0071] The pervaporation membrane prepared in Comparative Example 3 was used to separate a 15 wt.% N,N-dimethylformamide aqueous solution, and the permeation flux was 40.3 g·m -2 ·h -1 , the separation factor was 6.3. After 160 h of continuous operation, the permeation flux and separation factor began to change (decline).

[0072] The permeation flux and separation coefficient results of the membranes of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1.

[0073] Table 1

[0074] By comparing the data of the embodiments and comparative examples, it can be obtained that the addition of the MOF-on-MOF structure makes the mixed matrix membrane show higher permeation flux and separation factor than the single MOFs mixed matrix membrane. At the same time, the permeation flux and separation factor of the binary MOFs membrane with a core-shell structure are higher than the permeation flux and separation factor of the membrane simply mixed with two MOFs (Comparative Example 3).

[0075] pass Figures 1 to 3 It can be seen that the Zr-MOF@Cu-MOF prepared in Examples 1 to 3 of the present invention has Zr-MOF as the core, and Cu-MOF grows orderly on the surface of Zr-MOF, thus presenting a core-shell structure.

Claims

1. A pervaporation membrane doped with a MOF-on-MOF core-shell structure filler, characterized in that: It includes an organic polymer-based membrane and a Zr-MOF@Cu-MOF filler with a MOF-on-MOF core-shell structure dispersed in the organic polymer-based membrane.

2. The pervaporation membrane according to claim 1, characterized in that: The organic polymer base film is a composite film formed by polyvinyl alcohol and polyacrylic acid; wherein, in the composite film, the mixing mass ratio of polyvinyl alcohol to polyacrylic acid is 8 to 9:

1.

3. The pervaporation membrane according to claim 1, characterized in that: In the composite membrane, the doping amount of Zr-MOF@Cu-MOF filler is 1% to 5% of the total mass of polyvinyl alcohol and polyacrylic acid.

4. The method for preparing the pervaporation membrane according to claim 1, characterized in that: Specifically, polyvinyl alcohol, polyacrylic acid and water are mixed and heated to obtain a polyvinyl alcohol aqueous solution; Zr-MOF@Cu-MOF filler is added to the polyvinyl alcohol aqueous solution, stirred evenly to obtain a casting liquid, cast into a film, and solidified to obtain a pervaporation membrane.

5. The preparation method according to claim 4, characterized in that: The heating temperature is 80-90° C., and the heating time is 2-6 hours.

6. The preparation method according to claim 4, characterized in that: The curing temperature is 20-30° C., and the curing time is not less than 24 hours.

7. The preparation method according to claim 4, characterized in that: The Zr-MOF@Cu-MOF filler is prepared by the following method, which comprises the following steps: (1) Preparation of Zr-MOF: Dissolve zirconium tetrachloride and an organic ligand in N,N-dimethylformamide, mix well, add acetic acid, subject the mixed solution to a hydrothermal reaction at high temperature, wash and dry after the reaction to obtain Zr-MOF; (2) Zr-MOF is ultrasonically dispersed in DMF, and then copper nitrate, trimesic acid and DMF are added thereto. The mixed solution is subjected to a hydrothermal reaction at high temperature. After the reaction, the mixture is cleaned and dried to obtain Zr-MOF@Cu-MOF having a MOF-on-MOF core-shell structure.

8. The preparation method according to claim 7, characterized in that: In step (1), the organic ligand is one of terephthalic acid, 2-aminoterephthalic acid or 2,5-dihydroxyterephthalic acid; and the molar ratio of zirconium tetrachloride to the organic ligand is 0.5 to 3:

1.

9. The preparation method according to claim 7, characterized in that: In step (1), the temperature of the hydrothermal reaction is 120-125° C., and the hydrothermal reaction time is 70-72 h; in step (2), the temperature of the hydrothermal reaction is 120-120° C., and the hydrothermal reaction time is 96-98 h.

10. The preparation method according to claim 7, characterized in that: In step (2), the molar ratio of copper nitrate to trimesic acid is 3:1 to 1.5.